Thai Nurse Brand in 21st Century: Challenges for Nursing Profession - Somsap, Yaowares; Varee, Acha (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
In the twenty first century, there is a big leap in technology, economic, social, culture and healthcare. Because of the advanced technology led the clients easily access to medical information and healthcare services and also led to the higher expectations in medical and nursing services. This is the most challenge in nursing services for adaptation, and improvement. Including of making their own brands to meet their needs and expectations of the customers in the twenty first century. This article introduce to nursing brands in the twenty first century that consists of nursing brands in the twenty first century and trending in health care of the customers. Determination and development performance in nursing that consists of development in knowledge, skills of alternative medicine, understanding in cultural diversity, development in foreign language for alternative or complementary care, and skill of internet technology in nursing. All of these can lead Thai nurses for making their own brands and maintain identity and strengthen in nursing profession. Including presentation of the development sample of these potency in Bachelor of Nursing Science of McCormick Faculty of Nursing, Payap university.